Application of Yoga in the Treatment of Chronic Headaches - Barska-Kobylińska, Hanna; Byrska, Martyna; Janura, Marta; Weimann, Maja; Przywara, Grzegorz; Biegańska, Oliwia; Biczak, Emilia; Malaka, Ewa Katarzyna; Zubiak, Marlena; Langner, Sara (Quality in Sport, 2025)
Introduction Headaches represent a significant public health problem, ranking sixth among the most common causes of disability worldwide. They negatively affect the quality of life, particularly during the working years, leading to high economic costs. Despite their widespread prevalence, headaches are often underdiagnosed and inadequately treated, which exacerbates their negative impact on society. Aim of the Study The aim of this study is to evaluate the effectiveness of yoga in reducing the frequency, duration, and intensity of headaches, as well as improving the quality of life in patients suffering from migraines and tension-type headaches. This review aims to explore the potential for incorporating yoga as a complementary method in headache therapy. Materials and Methods The review includes the results of clinical studies examining the effects of yoga on migraines and tension-type headaches. The effects of yoga were compared with conventional treatment methods, considering improvements in pain parameters, stress levels, and patients’ psychological well-being. Conclusions Studies have shown that yoga effectively reduces the frequency and intensity of headaches and improves patients’ quality of life. It also reduces stress levels and enhances the balance of the autonomic nervous system. Combining yoga with pharmacological treatment yields better outcomes than conventional therapy alone. Further research is needed to evaluate the long-term effectiveness of yoga and to determine the optimal therapeutic parameters.